Biomechanics of Osteoporotic Fracture Care: Advances in Locking Plate and Intramedullary Nail Technology. (October 2021) - Aneja, Arun; Teasdall, Robert J.; Graves, Matt L.
Abstract : Summary: Osteoporotic fractures are extremely common and will continue to increase. Methods of internal fixation must address challenges presented by architectural changes of weakened bone. The goals of surgery are to provide mechanically stable internal fixation with minimal biologic insult that provides rapid rehabilitation and early mobilization. Novel techniques and technology that reinforce preservation of periosteal blood supply and utilization of biomechanically stable constructs diminish failure rates. Advents in locking plate technology, intramedullary nail designs, bone augmentation, and multiple implant constructs maximize strength while mitigating axial, torsional, and bending failure modes to provide optimal patient outcomes.